(untitled) (Journal of the College of Basic Education, 2023)
Some studies indicated that there is a positive relationship between general mental ability and academic achievement.This prompted specialists in the field of mental excellence to use the level of achievementThe academic study is mainly in defining and diagnosing the mentally superior. This trend is based onA fundamental issue is that the achievement of the individual in the past and the present is one of the most honest means ofPredicting his achievement in the future. Passow believes that excellence is the ability toExcellence in academic achievement, and both “Bentley” and “Stinquist” agree with it.(Stenqusit). Terman defined excellence in academic achievement by obtaining gradeshigher than the grades attained by 90% of the students, while “Fox” defined it as havinghigher than 95% of his classmates. (Morsi, 1981, pg. (52).There are several studies that dealt with excellence in achievement while talking about excellence.And what justifies its approach is the relationship that combines mental superiority and the remarkableIn achieving or excelling in it, the correlation coefficient between them is very high.Intelligence usually tends to outperform other students who are below it in achievement.General mental abilities. Therefore, high achievement is an indicator of intelligence, or it can be said that it isAn indicator of intellectual superiority. However, we notice in fact that there are quite a few studentsintellectually gifted, but they fall short in their academic achievement, as it is not surprising that we findThe academic performance of some outstanding students differs from their mental performance.The studies indicated that a percentage ranging between 10-20% of the students who dropped out of school areHigh achievers whose talents appeared early in their life (Zahlouk, 1997, p. 164) and moreOf the 30% of the dropouts who did not complete their secondary education, their IQ is greater than (135).And that many of the intellectually gifted were among the latecomers to their studies.(Webb & Others, 1982, p: 13-14). That is, the school performance of students may differ